Government Coordination In Implementing Stunting Weighing Operations In Kupang City - Hendrik Toda (Universitas Padjadjaran, 2024)
This study aims to determine Government Coordination in Implementing Stunting Weighing Operations in Kupang City. The type of research used is qualitative research. The research results show that the implementation of stunting operations in Kupang City involves cross-sectoral coordination. Availability of stunting toddler data as a result of carrying out operations as a basis for carrying out stunting interventions in Kupang City. Based on horizontal coordination, even though the leading sector is in the health office, coordination with equivalent institutions has been running optimally. However, vertical coordination is still a problem because the target for weighing (toddlers) at the community level involves community participation in load operations. Even though the level of attendance is relatively high, not all toddlers participate in these activities. Based on this, coordination between central, regional, and local government institutions needs further improvement. Apart from increasing coordination between governments, more effective community participation is also required. Inter-governmental coordination and community participation are the keys to success in dealing with the stunting problem in Kupang.